2012
DOI: 10.1007/s13157-012-0292-x
|View full text |Cite
|
Sign up to set email alerts
|

Field-Based Radiometry to Estimate Tidal Marsh Plant Growth in Response to Elevated CO2 and Nitrogen Addition

Abstract: Plant growth is one of the most important variables to measure in long-term research plots, but the negative effects of labor-intensive and destructive sampling can restrict frequent assessment of plant biomass. Here, we used field-based, active radiometry to assess plant biomass in an ongoing, experimental manipulation of atmospheric CO 2 and soil nitrogen availability in a tidal wetland. We compared the ability of several radiometric vegetation indices (VIs) to predict total plant biomass and that of two pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…One of the most important and extensive plants in the salt meadows of Tilopozo is S. americanus. However, Langley and Megonigal [49] indicated that determining the phenological stage of S. americanus using NDVI is very complex, because the biomass is brown, and this generates very low NDVI values, which can be interpreted as bare soil. In addition, as S. americanus plants increase in height, their leaf areas decrease, which impacts NDVI in a counterintuitive manner, because higher biomass leads to lower NDVI values [50].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important and extensive plants in the salt meadows of Tilopozo is S. americanus. However, Langley and Megonigal [49] indicated that determining the phenological stage of S. americanus using NDVI is very complex, because the biomass is brown, and this generates very low NDVI values, which can be interpreted as bare soil. In addition, as S. americanus plants increase in height, their leaf areas decrease, which impacts NDVI in a counterintuitive manner, because higher biomass leads to lower NDVI values [50].…”
Section: Discussionmentioning
confidence: 99%
“…Kirkpatrick Marsh, in the Rhode River sub-estuary along the northwestern shoreline of the Chesapeake Bay, is classified as an estuarine, emergent, persistent, and irregularly flooded marsh (E2EM1P) according to the National Wetlands Inventory (NWI) 2013 update. Kirkpatrick Marsh is noted as being high elevation by previous studies [46][47][48]. The vegetation composition is typical of a high elevation marsh in the Mid-Atlantic region of the United States with dominant species including: Scirpus americanus (also known as Shoenoplectus), Spartina patens, Iva frutescens, and Phragmites australis.…”
Section: Study Site Selectionmentioning
confidence: 96%
“…To evaluate how differences in geomorphology (i.e., marsh elevation) impact marsh inundation regimes and our ability to detect inundation using different remote sensing tools, our remote sensing assessment and mapping of marsh inundation focused on Kirkpatrick Marsh and Blackwater NWR. Kirkpatrick Marsh consists of almost entirely high marsh, is less frequently inundated than low marsh systems, and the mean tidal amplitude of the adjacent Rhode River sub-estuary is 0.3 meters [47,58,59]. This presented a unique opportunity to determine how effectively inundation events of low water depth (less than 0.5 meters) that occurred below dense vegetated canopies could be detected using satellite imagery, particularly in regions dominated by the high biomass and densely growing Phragmites australis.…”
Section: Field Measurements Of Marsh Inundationmentioning
confidence: 99%
See 2 more Smart Citations